Solidified floating organic drop microextraction in tandem with syringe membrane miro-solid phase extraction for sequential detection of thallium (III) and thallium (I) by graphite furnace atomic absorption spectrometry - Juntao Yan; Chenghao zhang; Chunlei Wang; Dengbo Lu; Shizhong Chen (Arabian Journal of Chemistry, 2022)
In the present study, a novel method based on solidified floating organic drop microextraction (SFODME) combined with syringe membrane micro-solid phase extraction (SMMSPE) was proposed for the sequential separation and enrichment of Tl(III) and Tl(I) followed by graphite furnace atomic absorption spectrometry detection. In SFODME, Tl(III) can react with 1-(2-Pyridylazo)-2-naphthol at pH 8.0 to form the complexes which can be extracted into an organic drop, while Tl(I) was remained in the solution. In SMMSPE, flexible TiO2@SiO2 nanofiber membrane was used as the sorbent for the enrichment of Tl(I) in the sample solution after the separation of Tl(III). This method did not require tedious pre-oxidation/pre-reduction operation and time-consuming centrifugation/filtration steps, which may cause sample contamination and analysis errors. Main parameters influencing the separation and enrichment of the target species were studied. Under the selected conditions, the detection limits for this method were 1.7 and 2.6 ng/L for Tl(III) and Tl(I) with relative standard deviations of 6.1 % and 5.2 %, respectively. This method was successfully used for the determination of the target species in environmental water samples and two certified reference materials. The determined values were in good agreement with the certified values.